Highly stable and tunable narrow-spacing dual-wavelength ytterbium-doped fiber using a microfiber Mach–Zehnder interferometer - Ahmad, Harith; Salim, M.A.M.; Azzuhri, Saaidal Razalli; Harun, Sulaiman Wadi (International Society for Optical Engineering (SPIE), 2016)
We describe a successful demonstration of highly stable and narrowly spaced dual-wavelength output via an ytterbium-doped fiber laser. A microfiber-based Mach-Zehnder interferometer and a tunable bandpass filter were both placed into the laser ring cavity for the purpose of ensuring a stable and narrowly spaced dual-wavelength output. Experimental results comprised three sets of dual-wavelength lasing output with wavelength spacing of 0.06, 0.09, and 0.22 nm, respectively, and side-mode suppression ratio of ∼50 dBm. A subsequent stability test provided evidence that maximum power and wavelength fluctuation were less than 0.8 dB and 0.01 nm, respectively, and thus, the obtained output was considered to be highly stable in dual-wavelength operation. The proposed system offers advantages of flexibility in dual-wavelength laser generation in addition to excellent reliability.